Kinematic Rhetoric Non-Discursive, Time-Affect Images in Motion - Murray, Joddy (Anthem Press, 2020)
Joddy Murray, in "Kinematic Rhetoric," puts forward a theory of rhetoric that adds the elements of movement, sound, image, affect and duration to traditional accounts of digital, visual and multimodal rhetorics. His concept of "time-affect" images provides a complex and nuanced theory for composing that builds upon his earlier concept of "nondiscursive texts." By turning to Deleuze's work on cinema, Murray presents the "time-affect image," which "generates" and amplifies affectivity through duration and motion, and is the key concept in this rhetorical theory. Motion, he argues, creates meaning that is independent of the content and, like all images, carries with it the potential for persuasion through the affective domain.